2020
DOI: 10.1016/j.heliyon.2020.e04940
|View full text |Cite
|
Sign up to set email alerts
|

Graduate students reported practices regarding the issue of informed consent and maintaining of data confidentiality in a developing country

Abstract: Research involving human subjects requires strict adherence to ethical principles, including informed consent and assuring data confidentiality. Herein, a questionnaire was utilized to assess compliance of graduate students who conduct research involving human subjects in Jordan with proper practices related to informed consent and maintaining of data confidentiality. Among the 251 respondents, 55.4% were from health-related fields, 61.4% undertook research involving humans, and 48.6% did research requiring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This attitude of health science faculty members towards integrating RCR mandatory course also suggests that the lack of postgraduate training in research ethics in Jordan extends to graduate programs from health science disciplines other than pharmacy. In further support of this, Swedan et al ( 2020 ) have reported in their multidisciplinary and multi-university survey that included graduate students performing human subjects research in Jordan that only 37% were exposed to RCR education (Swedan et al, 2020 ). Indeed, this type of RCR training was also deemed necessary for other research investigators, as previous studies in Jordan revealed that the majority (> 80%) of resident doctors, health sciences faculty members, and healthcare investigators have agreed that such training in research ethics is essential for clinical investigators, faculty affiliates, and IRB members in Jordan (Al Demour et al, 2019 ; Ayoub et al, 2019 ; Rababa'h et al, 2020 ; Tarboush et al, 2020 ), although graduate students reported more unfamiliarity and misconceptions regarding RCR topics (Rababa'h et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…This attitude of health science faculty members towards integrating RCR mandatory course also suggests that the lack of postgraduate training in research ethics in Jordan extends to graduate programs from health science disciplines other than pharmacy. In further support of this, Swedan et al ( 2020 ) have reported in their multidisciplinary and multi-university survey that included graduate students performing human subjects research in Jordan that only 37% were exposed to RCR education (Swedan et al, 2020 ). Indeed, this type of RCR training was also deemed necessary for other research investigators, as previous studies in Jordan revealed that the majority (> 80%) of resident doctors, health sciences faculty members, and healthcare investigators have agreed that such training in research ethics is essential for clinical investigators, faculty affiliates, and IRB members in Jordan (Al Demour et al, 2019 ; Ayoub et al, 2019 ; Rababa'h et al, 2020 ; Tarboush et al, 2020 ), although graduate students reported more unfamiliarity and misconceptions regarding RCR topics (Rababa'h et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Challenges/Issues Discussed [263] Healthcare Security and privacy [264] Healthcare Data intrepretation and fusion [265] Healthcare Security and privacy [266] Healthcare Informed consent [267] Healthcare Informed consent and confidentiality [268] Surveillance Privacy [269] Surveillance Security and privacy [270] Surveillance Privacy [271] Recruitment Privacy and informed consent [272] Generic Security, privacy, bias, and informed consent [273] Generic Informed consent [274] Recruitment Bias [275] Generic Bias [276] Generic Bias [62] Generic Open data, intrepretation, and annotation…”
Section: Ref Applicationmentioning
confidence: 99%
“…Students often have a close encounter with research ethics when they apply for their ethical clearance from their universities ( DePauw, 2009 ). Therefore, they need to be provided with ethics training through online modules, courses, or workshops to help them conduct responsible research ( Petillion et al, 2017 ; Swedan et al, 2020 ). There has been a growing interest in research ethics globally especially in the context of studies involving human participants ( Barrow et al, 2023 ; Burgess et al, 2023 ; Gefenas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, postgraduate students have complained about not receiving or receiving little training on how to conduct responsible research ( Vasgrid, 2007 ). This is changing because compulsory training on research ethics is now provided to postgraduate students ( Fisher, Fried, Goodman, & Germano, 2009 ; Swedan et al, 2020 ). The teaching of research ethics is done in diverse ways, including guest lectures, lectures, assignments, case studies, workshop, presentation, and online programmes ( Naimi, 2007 ; Petillion et al, 2017 ; Swedan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%